Effect of magnetic field on crack control of Co-based alloy laser cladding. (September 2021) - Qi, Kang; Yang, Yong; Sun, Rui; Hu, Guofang; Lu, Xin; Li, Jindong; Liang, Wanxu; Jin, Kang; Xiong, Li
Highlights: The magnetic field can reduce the crack sensitivity of the laser cladding layer. The pore in the cladding layer is sensitive to crack under compressive stress. CoFe phase helps to reduce the thermal stress of the laser cladding layer. The magnetic field can improve the microhardness of the laser cladding layer. Abstract: The Co-based laser cladding layer was prepared on the 42CrMo substrate. The magnetic field was applied during the laser cladding process. The causes of cracks and pores in the cladding layer are analyzed systematically. The magnetic field has a remarkable effect on the defect and properties of the cladding layer. The morphology evolution, phase composition, element distribution, thermal expansion, and thermal stress were investigated. The result indicates that the magnetostriction effect decreased thermal expansion and thermal stress in the magnetization-induced laser cladding process, which reduces the cladding layer's crack sensitivity. The cladding layer's average microhardness and morphology properties were increased to that of the cladding layer without the magnetic field-assisted. The magnetic field can improve the element distribution uniformity and lower the element segregation that the crack sensitivity of the cladding layer was reduced.